ANALISIS PENGARUH REPUTASI ORGANISASI DAN KINERJA KEUANGAN TERHADAP KONTRIBUSI ORGANISASI NIRLABA - Dara Ayu Ning Cahya Islami; Tarmizi Achmad (Diponegoro Journal of Accounting, 2017)
This study aims to examine the effect of reputation and financial performance to nonprofit contributions. Reputation as an independent variable measured by the age and the size of the non-profit organization, while financial performance is proxy through fiscal performance, public support, and program efficiency. For the independent variables, this study used total contributions acquired by non-profit organizations.This study tested using OLS regression with balanced panel data. The population of this study is all nonprofit organization in Indonesia in 2010-2014, with a sample of 15 non-profit organizations selected by using purposive random sampling. The criteria used in selecting the sample are a nonprofit organization that has a complete financial statement of 2010-2014 and presenting in Rupiah currency.The empirical results of this study indicate that the size of the organization and program efficiency have a positive influence to nonprofit contributions. By contrast, public support has a negative influence to the nonprofit contributions. While the age of the organization and fiscal performance did not influence the nonprofit contributions.